Shamba Shape-Up. Episode three: Homabay, Kenya (English) - Mediae (2015)
With the support of CGIAR Research Programs Water Land and Ecosystems (WLE) and Climate Change Agriculture and Food Security (CCAFS), CIAT sponsored five episodes of Kenya’s popular make-over TV series, Shamba Shape-Up, to advise farmers how to protect their soils.